Indoor Thermal Analysis of Hospital Building in Dire Dawa, Ethiopia - Bethelhem, Seifu (ASTU, 2021)
Thermal Comfort Is A Primary Concept In Human Life And Activity. In Addition To The environmental Parameters, The Concept Incorporate Psychological And Physiological aspects. The Vulnerability Of The Occupants To Elevated Temperatures Is One Of Accounting Factor For Thermal Susceptibility. Thermal Comfort Is a Sensitive Issue in hospital Buildings, Indicating the Necessity for a Thorough Study. Aside From That, Due to Their Health-Related Consequences, Patients Are Likely To Have Varied Thermal requirements. This Study, Therefore, Aims To Evaluate The Indoor Thermal Comfort Of two Hospital Buildings In Dire Dawa. There Wasn??T Any Study Done In Dire Dawa, Ethiopia On The Thermal Comfort Assessment In Hospital Buildings. In This Study, Three environmental Factors(Indoor Air Temperature, Air Speed, And Relative Humidity)Measured And Analyzed To Determine Their Level Relative To ASHRAE 55 Standard, The value Of Environmental Variables Compared With Occupants (Clinical Staf , Patients, And Visitors) Perception Towards Thermal Comfort. The Physical Measurement And survey Were Carried In The Warmest Month Of The Year, From Mid-April To May2021G.C. For Six Selected Room Of The Case Buildings. The Data Obtained From The survey Was Analyzed Using SPSS Version 24 And MS Excel. The Result Of The Study revealed That Almost All Occupants Are Not Comfortable With The Indoor Thermal condition And Prefer Cooler Environment. Thermal Perception Of 57.3% Of occupants Is Out Of The Comfort Zone Of ASHRAE 55. The Average Mean Temperature Is29.80C And Humidity Is 38%. The Air Velocity Data Is Also Below The Comfort Range. According To the Result High Temperature and Low Air Velocity Highly Afect The building Space, With 62% And & 75% Probability Of Affecting The Thermal Perception of Occupants. The Building Fail To Modify The Micro Climate Of The Study Area. Passive building Techniques Which Can Avoid Excess Heat And Allow Better Ventilation System are Suggested. In Addition To That Building, Regulations Need To Incorporate Thermal comfort Requirements, Particularly In Design And Construction Of Medical environment.
Indoor Thermal Analysis Of Hospital Building In Dire Dawa, Ethiopia
Keywords: Hospital building, Indoor space, Thermal preference, Comfort zone, Bio-climatic; Hospital Building, Indoor Space, Thermal Preference, Comfort Zone, Bio-Climatic